Methodology in Science and Religion: A Reply to Critics - Reeves, Josh A. (Zygon, 2020)
Debates about methodology have been central to the emergence of the “field of science of religion.” Two questions that have motivated scholars in that field over the past half century: “is it theoretically justifiable to bring scientific and religious beliefs into dialogue?” and “can theology be rational in the same way as science?” This article responds to commentary on Against Methodology: Recent Debates on Rationality and Theology, a book which critically examines three major methodologists of recent years: Nancey Murphy, Alister McGrath, and J. Wentzel van Huyssteen. Themes raised in the commentary include the status of realism and truth in science, the unity of science, the adequacy of the term “critical realism,” proper ways of seeking legitimacy for an academic discipline, and new directions for the field of science and religion.